Computer games and information-processing skills. - Yuji, Hiroki (Perceptual & Motor Skills, 1996)
To assess the association of past use of computer games and parallel-processing skills as measured by tests of discrimination perception using computers 46 boys and girls in kindergarten, aged 4 to 6 years, were classified into 17 player and 17 nonplayer groups by their enthusiasm for computer games. There were no significant differences between the two groups in correct responses; however, RTs of players were significantly faster than those of nonplayers. RTs were different to color and shape. Experiences with computer games might develop information-processing skills. Reprinted by permission of the publisher, 1996.